Chemical composition of nutmeg and mace - GOPALAKRISHNAN, M (Journal of Spices and Aromatic Crops, 1992)
The proximate analysis of nutmeg and mace, unlike in most earlier reports, has been carried out using the raw spices. The major hallucinogenic principle in Indian nutmeg/mace oils appears to bemyristicin which is present in good amount. GC profiles of the oils compared very well with reports in Ii terature. The rind ofthe nutmeg fruit con tain good quality pectin upto 14%.